SEWA TANAH PERTANIAN DI NAGORI PERLANAAN KECAMATAN BANDAR KABUPATEN SIMALUNGUN (STUDI ANALITIS DARI PERSPEKTIF HUKUM YUSUF QARDHAWI) - Sirait, Nilna Mayang Kencana (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
This paper aims to critically analyze the phenomenon of agricultural land rent in Nagori Perlanaan, Bandar-Simalungun through Yusuf Qardhawi's Law perspective. The research is field research, where the data collection methods are: Observation, Interviews and documentation. The study found that the phenomenon of agricultural land rent in Nagori Perlanaan was with money. From Qardhawi's view, this practice is prohibited. The reason is that there is a prohibition from several prophetic traditions (hadits). In addition, this method contains elements of injustice and vagueness. Such method cannot be excluded with other rental models such as house, vehicles and so on. In this context, the muzâra'ah system or profit sharing is more appropriate, because tenant farmers are more protected and guaranteed.